2018
DOI: 10.3389/fpls.2017.02217
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Causes Oxidative Stress and Tapetal Apoptosis in Chemical Hybridization Reagent-Induced Male Sterility in Wheat

Abstract: Male sterility in plants has been strongly linked to mitochondrial dysfunction. Chemical hybridization agent (CHA)-induced male sterility is an important tool in crop heterosis. Therefore, it is important to better understand the relationship between mitochondria and CHA-induced male sterility in wheat. This study reports on the impairment of mitochondrial function duo to CHA-SQ-1, which occurs by decreasing cytochrome oxidase and adenosine triphosphate synthase protein levels and theirs activities, respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…Many studies suggested that the over-accumulation of ROS can also affect the expression of various genes by oxidative damage [ 42 , 43 ]. Moreover, previous studies on the mitochondrial genome have revealed some genes or open reading frames (ORFs) are often chimeric and co-transcribed with genes that encode the mitochondrial subunits of the respiratory enzymes related to ROS release and further indicated that mutation and recombination have a direct relationship with CMS [ 20 , 44 , 45 ]. In our study, we performed RT-PCR to determine the expression levels of the genes encoding important antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested that the over-accumulation of ROS can also affect the expression of various genes by oxidative damage [ 42 , 43 ]. Moreover, previous studies on the mitochondrial genome have revealed some genes or open reading frames (ORFs) are often chimeric and co-transcribed with genes that encode the mitochondrial subunits of the respiratory enzymes related to ROS release and further indicated that mutation and recombination have a direct relationship with CMS [ 20 , 44 , 45 ]. In our study, we performed RT-PCR to determine the expression levels of the genes encoding important antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…TM resulted in BCAA starvation by anther-specific acetolactate synthase ( ALS ) inhibition and autophagic cell death in anthers [ 9 ]. The oxidative stress and overexpression of type II metacaspase in SQ-1 treated wheat would trigger premature tapetal apoptosis, and then result in pollen abortion [ 12 , 13 ]. Here, we found the new ALS inhibitor SX-1 can be used as an effective CHA to induce male sterility in B. napus .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CIMS doesn’t need prior selecting to match maintainer and restorer lines like CMS or remove the fertile plants from the female parents as half offspring of GMS are fertile [ 7 ]. Therefore, CHAs are getting more and more attention and have been widely applied, such as tribenuron-methyl (TM) [ 8 , 9 ], monosulphuron ester sodium (MES) [ 10 , 11 ] in B. napus and SQ-1 in Triticum aestivum [ 12 , 13 ]. In MES induced male sterility, genes involved in cellular transport, lipid and carbohydrate metabolism were differentially expressed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the molecular mechanism underlying SQ-1-induced wheat male sterility remains relatively unknown, representing an impediment to the application of SQ-1-induced wheat male sterility. Previous research has indicated that pollen abortion may be associated with impaired energy metabolism after spraying of SQ-1 [17][18][19][20][21][22][23]. For example, SQ-1-induced sterility lines showed lower expression levels of the PDH-E1α gene, which is essential for regulation of the tricarboxylic acid (TAC) cycle [24].…”
Section: Introductionmentioning
confidence: 99%